PHARMACEUTICALS AND ENDOCRINE-DISRUPTING COMPOUNDS: ACCUMULATION IN THE TISSUE OF SKADAR LAKE FISH - Radonjić, Dražana (Bulletin of Natural Sciences Research, 2021)
Determining the presence of pharmaceuticals and endocrine-disrupting compounds in fish tissues has been carried out in Montenegro for the first time in Moraca river and Skadar lake. Skadar lake, Montenegro, is the largest of the Balkan lakes and has a surface area which fluctuates seasonally from approximately 370 to 600 km2. During the spring time of 2016, in the time of high water levels of the lake, fish were fetched in triplets and identified.  Determining the presence of pharmaceuticals and endocrine-disrupting compounds in fish tissues has been carried out in Montenegro for the first time. Their muscle tissue was separated, grinded, feezed, and then lyophilized.  Prepared samples were analyzed with liquid chromatography coupled to tandem mass spectrometry to determine the presence of pharmaceuticals and endocrine-disrupting compounds. Obtained results are under the border of detection, out of 38 tested distributes, only the tissue of Alburnus scoranza showed the presence of triclosan.
Keywords: Endocrine-disrupting compounds; Lyophilized; Liquid chromatography coupled to tandem mass spectrometry; Alburnus scoranza; Triclosan